PENGARUH LIKUIDITAS, SOLVABILITAS, MANAJEMEN ASET, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Diana, Lely; Osesoga, Maria Stefani (Jurnal Akuntansi Kontemporer, 2020)
Financial performance refers to companies capability which is showed in financial report and used for decision making by stakeholders. The objective of this research was to obtain empirical evidence about the effect of liquidity, solvency, management asset, and firm size towards financial performance. The object in this research were manufacturing companies listed in Indonesia Stock Exchange (IDX) for period 2015-2018. The sample was selected by using purposive sampling method. The secondary data used in this research was analyzed by using multiple regression method. The result of this research were (1) liquidity have significant effect towards financial performance, (2) solvency does not have effect towards financial performance, (3) management asset have significant effect towards financial performance, (4) firm size does have significant effect towards financial performance.